“NGAMUMULE BUDAYA SUNDA JATUKRAMI”: ENHANCING CULTURAL LITERACY FOR BRIDAL MAKEUP ARTIST - Retno Dwi Lestari; Elais Retnowati; Elsa Fitri Ana; Annisa Ramadhanty; Fathia Maharani (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract More than four thousand Bridal Makeup Artists are members of the Indonesian Bridal Makeup Experts Association (HARPI) Melati, West Java, Indonesia. However, less than 5% of them are aware of the meaning, messages, and implied values in traditional West Javanese Bridal. This condition has led to many traditional West Javanese bridal appearances that do not align with their philosophy. Based on this, the Community Service activity offers a cultural literacy workshop on traditional bridal customs for bridal makeup artists in West Java through Work Integrated Learning (WIL). The WIL model allows the workshop to be designed by integrating the theoretical cultural values of traditional West Javanese bridal customs with practice-based learning. The approach used Seminar and Competition with the theme “Ngamumule Budaya Sunda Jatukrami” using methods such as 1) lectures, 2) simulation, 3) practice, and 4) discussions. The teaching material used in this workshop is the book “From Philosophy to Innovation: Garut RA Lasminingrat Bridal Makeup”. This activity resulted in an increased understanding and competence among bridal makeup artists, making them more innovative, productive, and collaborative in preserving the cultural values of West Javanese bridal. Keywords: Work Integrated Learning, Competency, Traditional Bridal Cultural Literacy Abstrak Lebih dari empat ribu Penata Rias Pengantin adalah anggota Himpunan Ahli Rias Pengantin Indonesia (HARPI) Melati, Jawa Barat, Indonesia. Namun, kurang dari 5% di antara mereka yang memahami makna, pesan, dan nilai-nilai tersirat dalam rias pengantin tradisional Jawa Barat. Kondisi ini menyebabkan banyak tampilan pengantin tradisional Jawa Barat yang tidak selaras dengan filosofinya. Berdasarkan hal ini, kegiatan Pengabdian Masyarakat dilaksanakan melalui seminar literasi budaya tentang adat pengantin tradisional untuk penata rias pengantin di Jawa Barat melalui Work Integrated Learning (WIL). Model WIL mampu mengintegrasikan nilai-nilai budaya teoretis adat pengantin tradisional Jawa Barat dengan pembelajaran berbasis praktik. Kegiatan diselenggarakan dengan tema "Ngamumule Budaya Sunda Jatukrami" melalui metode seperti 1) ceramah, 2) simulasi, 3) praktik, dan 4) diskusi. Materi pengajaran yang digunakan dalam seminar ini adalah buku "Dari Filosofi ke Inovasi: Rias Pengantin Garut RA Lasminingrat". Kegiatan ini menghasilkan peningkatan pemahaman dan kompetensi di kalangan penata rias pengantin, sehingga mereka menjadi lebih inovatif, produktif, dan kolaboratif dalam melestarikan nilai-nilai budaya pengantin tradisional Jawa Barat. Kata Kunci: Work Integrated Learning, Kompetensi, Literasi Budaya Pengantin Tradisional